(untitled) (International Journal of Banking and Finance, 2010)
Using return data for all stocks continuously traded on the NYSE over the period July 1963 to December 2006, we tested the performance of the two-moment Capital Asset Pricing Model (CAPM) and the Fama French three-factor model in explaining individual stock returns. We found the performance of Fama French three-factor model to be marginally better than the CAPM. We further test the models for the significance and stability of parameters in the bull/bear periods and the Federal increasing/decreasing interest rate periods and found the performance of the two models comparable.